I would go with D. Hope that helps :)
Answer:
Here
Step-by-step explanation:
We move all terms to the left:
7+9x-(6x-2)=0
We get rid of parentheses
9x-6x+2+7=0
We add all the numbers together, and all the variables
3x+9=0
We move all terms containing x to the left, all other terms to the right
3x=-9
x=-9/3
x=-3
Answer:
x¹²,8x⁴,6x,2x,1
Step-by-step explanation:
x²×x⁶×x⁴=x¹²
x^4(8) =8x⁴
x^1(6) =6x
x^1(2) =2x
x^0 = 1
Answer:
Step-by-step explanation:
Let the two numbers be 2x and 3x.
According to the question,
2x+3x=45
5x=45
x=45/5
x=9
so th required numbers are 18 and 27 as
2x=2*9=18
3x=3*9=27
Answer:
oh ok.. can i get ur intro??